Amino-functionalized poloxamer 407 with both mucoadhesive and thermosensitive properties: preparation, characterization and application in a vaginal drug delivery system - Liqian Ci; Zhigang Huang; Yu Liu; Zhepeng Liu; Gang Wei; Weiyue Lu (Acta Pharmaceutica Sinica B, 2017)
Lack of mucoadhesive properties is the major drawback to poloxamer 407 (F127)-based in situ hydrogels for mucosal administration. The objective of the present study was to construct a novel mucoadhesive and thermosensitive in situ hydrogel drug delivery system based on an amino-functionalized poloxamer for vaginal administration. First, amino-functionalized poloxamer 407 (F127-NH2) was synthesized and characterized with respect to its micellization behavior and interaction with mucin. Then using acetate gossypol (AG) as model drug, AG-loaded F127-NH2-based in situ hydrogels (NFGs) were evaluated with respect to rheology, drug release, ex vivo vaginal mucosal adhesion, in vivo intravaginal retention and local irritation after vaginal administration to healthy female mice. The results show that F127-NH2 is capable of forming a thermosensitive in situ hydrogel with sustained drug release properties. An interaction between positively charged F127-NH2 and negatively charged mucin was revealed by changes in the particle size and zeta potential of mucin particles as well as an increase in the complex modulus of NFG caused by mucin. Ex vivo and in vivo fluorescence imaging and quantitative analysis of the amount of AG remaining in mouse vaginal lavage all demonstrated greater intravaginal retention of NFG than that of an unmodified F127-based in situ hydrogel. In conclusion, amino group functionalization confers valuable mucoadhesive properties on poloxamer 407.